Using landscape approaches to improve the integration of wildlife in forest management plans - Vliet, N. van; Nasi, Robert (2008)
Logging concessions can affect wildlife populations through indirect or direct effects. However, if wildlife is appropriately taken into account in the forest management plans, then logging concessions can become an opportunity for conservation, as they can play a crucial role as buffers around protected areas. In the last decade, large blocks of the Gabonese forests have been surveyed by logging companies to implement the new forestry law. Large data sets were generated with this information but little was done in terms of analysis. In this study we show that this invaluable data, collected during routine management planning processes, can be used to understand the landscape factors that explain mammal distribution in logging concessions and provide very useful recommendations for taking wildlife populations into account in logging operations.